Perubahan Fisiologis Pada Permainan Esports Kompetitif: Studi Esports Berbasis Mobile - Kurniawan, Tian; Ali, Rizki Hazazi; Ismanda, Shelly Novianti; Abdurahman, Muhammad Naufal; Rimasa, Dery (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2023)
Physiological aspects have been found affected during and following eSports activity especially on computer-based eSports. There are still lack of studies that mentioned physiological changes on mobile-based eSports. This study aims to investigate how mobile-based eSports (Mobile Legend) affecting some physiological aspects during and post gaming competition in college student. 20 players from 4 teams participated in a competition and then became the sample of this study. Heart rate and energy expenditure, were recorded as physiological aspects. Based on previous studies, we hypothesized that mobile-based eSports also affecting physiological aspects.